2019
DOI: 10.1111/nep.13508
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis reveals novel hub genes and pathways associated with hypertensive nephropathy

Abstract: Aim Hypertensive nephropathy (HTN) is one of the leading causes of end‐stage renal disease and is closely associated with inflammation and tubule‐interstitial fibrosis. The molecular mechanism underlying HTN remains unclear. This study used bioinformatic analysis to identify the novel gene targets for HTN. Methods We downloaded the microarray data of GSE99325 and GSE32591 from Gene Expression Omnibus. The dataset comprised 20 HTN and 15 normal samples. The differentially expressed genes (DEG) were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…With the development of sequencing techniques and bioinformatics, more mechanisms underlying HTN have been disclosed. The novel pivotal genes have been initially identified through microarray data using bioinformatic analysis [ 82 ]. Ferroptosis has been found to play a role in HTN through pathways such as branched-chain amino acid metabolism and retinol metabolism, and biological processes such as organic and amino acid metabolism and humoral immunity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of sequencing techniques and bioinformatics, more mechanisms underlying HTN have been disclosed. The novel pivotal genes have been initially identified through microarray data using bioinformatic analysis [ 82 ]. Ferroptosis has been found to play a role in HTN through pathways such as branched-chain amino acid metabolism and retinol metabolism, and biological processes such as organic and amino acid metabolism and humoral immunity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced DUSP1, DUSP4, DUSP6, DUSP10, and DUSP26 expression has been reported in diabetic nephropathy [32][33][34]. DUSP1 and DUSP5 are downregulated in hypertensive nephropathy [35,36],…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an early methodological innovation [ 64 ], researchers integrated the differential expression attribute of genes with information on pathway member sharing and showed that groups at the pathway interfaces were more relevant to leukemia subtype distinction. In another example of bioinformatics analysis of hypertensive nephropathy [ 65 ], the authors used a functionality through GOSemSim [ 66 ] to sketch a function term connection network, whereby they focused attention to genes associated with the bridging terms (terms forming the boundaries of network modules). In the present study, we laid out a differential-network-assisted pathway crosstalk analysis workflow ( Figure 1 ), demonstrating its validity in mining SCZ-relevant rewired pathways, disrupted pathway crosstalk circuits, and critical genes and gene links.…”
Section: Discussionmentioning
confidence: 99%